EFEKTIFITAS PELATIHAN KEPEMIMPINAN DAN MANAJEMEN BAGI KETUA TIM TERHADAP KEPUASAN PASIEN DI METRO HOSPITALS CIKUPA KABUPATEN TANGERANG - Sirait, Jesman Jhonny; Tarigan, Emiliana; Supardi, Sudibyo (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
Leadership in nursing management will affect the quality of nurse services and patient satisfaction, seen from access, effectiveness, efficiency, safety and security, continuity of service, and service standards to patients. This study aims to identify the effectiveness of Leadership and Management training for team leaders on patient satisfaction, using a Pre-experiment two groups post test design at Metro Hospitals Cikupa on 11 June - 11 August 2021. The team leader trained as many as 20 nurses and 9 nurses in the control group. The impact of the training was assessed based on satisfaction with 393 hospitalized patients in both groups. Data collection tools are questionnaires and Chi-Square Test Data Analysis and Multivariate Logistic Regression Test. The results showed that the satisfaction of inpatients based on 5 dimensions (tangibles, empathy, reliability, responsiveness, assurance) the largest percentage of the intervention group was satisfied and the control group was the largest quite satisfied. The effect of training was statistically significant (p<0.05). Inpatients in the intervention group had 8.5 times higher probability of satisfaction than patients in the control group. Patient characteristics, namely age, education, occupation and class of care were significantly related to inpatient satisfaction (p<0.05). This study recommends ongoing leadership and management training for all team leaders in the hospital, continuous monitoring and evaluation of patient satisfaction.